Performance Benchmarking of Key-Value Store NoSQL Databases - Omoruyi Osemwegie; Kennedy Okokpujie; Nsikan Nkordeh; Charles Ndujiuba; Samuel John; Uzairue Stanley (Institute of Advanced Engineering and Science, 2018)
Increasing requirements for scalability and elasticity of data storage for web applications has made Not Structured Query Language NoSQL databases more invaluable to web developers. One of such NoSQL Database solutions is Redis. A budding alternative to Redis database is the SSDB database, which is also a key-value store but is disk-based. The aim of this research work is to benchmark both databases (Redis and SSDB) using the Yahoo Cloud Serving Benchmark (YCSB). YCSB is a platform that has been used to compare and benchmark similar NoSQL database systems. Both databases were given variable workloads to identify the throughput of all given operations. The results obtained shows that SSDB gives a better throughput for majority of operations to Redis’s performance.